Emotional Literacy In An Era Of Anxiety: Integration Of Mental Health Into The Elementary School Curriculum - Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
This study aims to explore the implementation of emotional literacy and mental health integration in the elementary school curriculum, focusing on their impact on children's social, emotional, and academic development. The study was conducted at SD Negeri 10 Makassar using a qualitative approach using a case study design. Data were collected through interviews with the principal, teachers, and students, as well as direct observation of the implementation of emotional literacy and mental health. The results indicate that although there have been efforts to introduce emotional literacy, its implementation is still limited to ad-hoc activities and has not been systematically integrated into the curriculum. Mental health integration is also still responsive to emerging problems, rather than structured prevention. Some challenges faced include limited time within the curriculum, lack of training for teachers, and stigma surrounding mental health issues. However, there is significant potential to improve this education system with better training support for teachers and a change in school culture that is more open to mental health issues. This research is expected to contribute to the development of a more holistic curriculum, one that focuses not only on academic achievement but also on students' emotional and psychological well-being.